Strategic Management for Achieving Competitive Advantage: A Multiple Case Study - Mohammad Faried Wajdie Al As’adie; Ahmad Tanzeh; Nur Efendi (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
This study explores how strategic management contributes to achieving sustainable competitive advantage in Islamic educational institutions through a comparative multiple-case study of MAN 1 Jombang and SMA Trensains Tebuireng. A qualitative research approach with a multiple-case study design was employed to examine strategic environmental analysis, strategy formulation, strategy implementation, and strategic evaluation in two institutions operating under different governance structures and educational philosophies. Data were collected through semi-structured interviews, participant observation, and document analysis, and were analyzed using the interactive model of data condensation, data display, and conclusion drawing supported by cross-case analysis. The findings reveal that MAN 1 Jombang develops competitive advantage through bureaucratic legitimacy, structured strategic planning, systematic implementation, and performance-oriented evaluation, while SMA Trensains Tebuireng achieves competitiveness through intellectual differentiation, philosophical coherence, collaborative implementation, and reflective organizational learning. Despite these differences, both institutions demonstrate that sustainable competitive advantage emerges from the integration of strategic environmental analysis, strategic positioning, strategic resource utilization, implementation supported by leadership and organizational culture, and continuous evaluation. The study proposes the Strategic Competitive Advantage Model of Islamic Education, which explains that institutional competitiveness is strengthened through the dynamic interaction of these four strategic management processes, resulting in enhanced institutional reputation, academic excellence, public trust, organizational legitimacy, and long-term sustainability.